Formulasi dan Penentuan Stress Testing Sediaan Krim M/A dan A/M Ekstrak Etanol Edamame (Glycine max) (Formulation and Stress Testing of Ethanol Extract Edamame (Glycine max) O/W and W/O Cream) - Oktavia Catur Xenograf; Budipratiwi Wisudyaningsih; Siti Muslichah; Moch. Amrun Hidayat (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Edamame is a species of soybean (Glycine max) that contains isoflavone which has tyrosinase inhibitory activity. The aims of this study were to determine the effect of formulation on genistein content and the effect of storage temperature (25 °C and 50 °C) on oil in water (o/w) and water in oil (w/o) cream physicochemical characteristics (viscosity, spreadability, and pH). Genistein level was determined using thin layer chromatography (TLC) densitometry method and stability test was determined using stress testing method. The result showed that formulation gave no effect on genistein content in o/w and w/o cream with recovery values of 95.4178 ± 2.2815 % and 101.8276 ± 5.0063 %, respectively. The storage at 25 °C gave no effect on physicochemical characteristic, while the storage at 50 °C decreased viscosity value and increased spreadability value of cream. Keywords: edamame, isoflavone, cream, stress testing